An Application of Activity Based Costing Method as Alternative to Prices Laparatomy in Hospital the True Partner of Medan - Ali Napiah Nasution; Ermi Girsang; Vijay Dhillon (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Ileus is an occlusion or paralysis of the intestine that prevents the forward passage of intestinal contents, causing accumulation proximal to the site of the blockage. The problem of cost distortion can be avoided by using an activity-focused cost accounting method, namely the ABC (Activity-Based Costing) method. The ABC method uses more cost drivers than traditional cost accounting methods. The purpose of this study was to determine the application of the activity-based costing method as an alternative to laparotomy rates at Mitra Sejati Hospital Medan. The real cost of laparotomy with a diagnosis of obstructive ileus at Mitra Sejati General Hospital Medan is Rp. 26,875,905.00. There is a difference in the cost of a laparotomy with a diagnosis of obstructive ileus with a unit cost using the activity-based costing method and using real cost calculations at Mitra Sejati General Hospital Medan in 2020 with a cost difference of Rp. 2,804,156.3.